Glucose,cholesterol,total proteins and insulin-like growth factor typeI values in the follicular fluid of female river buffaloes (Bubalus bubalis) - Gallego, Carlos; Prado, Margarida [UNESP]; Camargos, Aline; Sousa, Diego [UNESP]; Souza, Maria Inês Lenz; Ramos, A. A. [UNESP]; Landim, Fernanda da Cruz [UNESP]; Oba, Eunice; Jorge, André Mendes [UNESP] (My University, 2012)
Twenty six Murrah female river buffaloes, between 45 and 70 d post-partum, empty, multiparae, with an average live weight of 675 ± 56 kg, and average body condition of 3.5 points, in a 1 to 5 scale, were used to determine the concentrations of glucose, cholesterol, total protein and insulin-like growth factor type I(IGF-I) in the follicular fluid. The fluid was collected from dominant follicles, with diameters between 8 and 12 mm, by in vivo follicular aspiration. The oestrous cycle stage was not taken into account. The wave of follicular development was synchronized six days prior to the collection. Biochemical analyses of glucose and cholesterol were performed by the enzymatic colorimetric method with the utilization of commercial kits of Glicose (GOD-PAP) and Cholesterol (CHOD-PAP) (Kovalent), respectively. For the determination of total protein, the commercial kit total Protein (Kovalent), method Biuret, was employed. Readings were carried out through absorption spectrophotometry with visible light. Through the radioimmunoanalysis (RIA) technique the concentration of IGF-I was obtained using commercial kits of IRMA IGF-I (IMMUNOTECH). Descriptive statistics was used, by applying the PROC MEANS procedure of the SAS (2009) statistical package. Glucose concentrations (4.0 ± 0.75 mmol/L) and IGF-I (340 ± 129.83 ng/mL) showed higher values in female river buffaloes and dairy cows regarding those reported in other studies. However, cholesterol levels (0.51 ± 0.12 mmol/L) and total proteins (58.4 ± 4.43 g/L) were lower. Results indicate that there is a relationship between the concentration of biochemical indicators, the nutritional aspects, the diameter of the aspired follicles and the productive period.
Keywords: Biochemical profile; Follicular fluid; Post-partum